Three stages of interpreting in Japan’s criminal process - Marszalenko, Jakub E. (Language and Law / Linguagem e Direito, 2017)
There are three main stages in Japan’s criminal process involving interpreters: interrogations by the Police, interviews conducted by the Public Prosecutors OXce, and the criminal trial, heard either by a professional judge (or judges) alone, or together with the so-called ‘lay judges.’ Even though these three stages may eventually form a single judicial process, the expectations of the interpreter, as well as the interpreting techniques, vary, thus making legal interpreting in Japan a multi-faceted and demanding endeavor. This paper gives an overview of the Japanese legal interpreting process exploring the various aspects that emerge during the three stages.